The Relationship Between Individual and Organizational Factors with the Performance of Nurses in the Surgical Ward - Rida' Millati (CV. Get Press Indonesia, 2024)
This study aimed to analyze the relationship between individual and organizational factors and the performance of nurses in the surgical ward of Dr. M. Djamil Padang Hospital. The problem addressed how individual variables, including nurses’ motivation and skills, and organizational factors, such as work culture and managerial support, influence nurse performance in surgical ward. The purpose of this study was to identify the most significant factors contributing to improve nurse performance in the surgical ward environment. A quantitative approach with a cross-sectional design was applied. The sample consisted of 60 nurses working in the surgical ward, selected using random sampling. Data were collected using structured questionnaires measuring individual factors, organizational factors, and nurse performance. Multiple linear regression analysis was conducted to assess the effect of each independent variable on nurse performance. The results showed that individual factors, namely motivation and skills, contributed 35% to nurse performance, while organizational factors, including managerial support and work culture, contributed 45%. Overall, the regression model explained 70% of the variance in nurse performance (R² = 0.70). Managerial support had the strongest influence (β = 0.38), followed by nurses’ motivation (β = 0.25).